2005
DOI: 10.1097/01.ijg.0000145814.46848.76
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Elasticity and Baroreflex Sensitivity in Patients With Glaucoma

Abstract: Our results suggest that in patients with chronic open-angle glaucoma the arterial rigidity is significantly increased and therefore the baroreflex function is significantly decreased. These findings may have relevance in the understanding of the autonomic dysfunction and vascular dysregulation in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Arterial stiffness is considered an independent predictor of cardiovascular disease, 65 and increased IMT has been suggested as an indirect measure of generalized atherosclerosis and cardiovascular risk. 66 The presence of cardiovascular disease and structural vascular wall changes has been variably linked to the presence of GON during recent years, with some studies identifying strong associations in POAG [67][68][69] and NTG 39,70,71 patients individually and others revealing no such associations. [72][73][74][75] The variability in results between these previous studies could in part be accounted for by differences in the inclusion/exclusion of patients with already diagnosed systemic vascular disease, especially because arterial stiffness is a measure of vascular function.…”
Section: Commentmentioning
confidence: 99%
“…Arterial stiffness is considered an independent predictor of cardiovascular disease, 65 and increased IMT has been suggested as an indirect measure of generalized atherosclerosis and cardiovascular risk. 66 The presence of cardiovascular disease and structural vascular wall changes has been variably linked to the presence of GON during recent years, with some studies identifying strong associations in POAG [67][68][69] and NTG 39,70,71 patients individually and others revealing no such associations. [72][73][74][75] The variability in results between these previous studies could in part be accounted for by differences in the inclusion/exclusion of patients with already diagnosed systemic vascular disease, especially because arterial stiffness is a measure of vascular function.…”
Section: Commentmentioning
confidence: 99%
“…[30][31][32][33][34] In a previous study using this technique we were able to identify increased arterial stiffness and decreased baroreflex function in juvenile and primary open angle glaucoma. 35 In the present study, in order to investigate systemic arterial function in XFS/XFG, using the ultrasound wall tracking system we measured end diastolic diameter and pulsatile distension of the common carotid artery, and calculated baroreflex sensitivity (BRS) in XFS/XFG patients and in normal control subjects of similar age. In addition, we tried to identify possible relations between BRS, age, and plasma homocysteine concentration in the two groups of subjects.…”
mentioning
confidence: 99%
“…The Rotterdam study reported that hightension or normal-tension OAG is related to high pulse pressure, low diastolic perfusion pressure and high diastolic BP (13). Chronic OAG is associated with increased arterial rigidity and decreased baroreflex function (44). Derived central BP is not altered in glaucoma, but a reduced pulse pressure was identified (7).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of arterial stiffness components has been investigated in certain other ophthalmic disorders, mainly in glaucoma (7,9,13,28,30,32,36,37,44) but not in refractory disorders. Several studies have shown impaired vascular endothelial function in patients with normal-tension glaucoma (NTG) reporting that atherosclerotic cerebrovascular disease involves the eye vasculature by small artery occlusion and therefore, it is a risk factor for having glaucomatous optic disk appearance (9,36).…”
Section: Discussionmentioning
confidence: 99%